The Role of Traditional Government in Mangrove Forest Management (Case Study of Women's Forest Management in Enggros Village, Jayapura City) - Fransiska Rosari Clarita You; Halilul Khairi; Jona Bungaran Basuki Sinaga (INFOKUM, 2025)
Customary forests cannot be separated from the existence of indigenous communities that have settled there since ancient times. The habits that are carried out often become a derivative of traditions that have lasted from time to time. Nowadays, with the reason of development, customary forests are finally opened to build buildings. In the Youtefa Bay Nature Tourism Park (TWA) it has become a conservation area, but it has become a place that receives pressure from development and waste that flows with high frequency. Moreover, indigenous communities who receive gifts of waste from the city and are directly affected in Enggros Village. Thus, the role of the Customary Government and Enggros Indigenous Women is actually very important to maintain the Women's Forest and manage the Women's Forest in Enggros Village, Jayapura City so that it remains sustainable. This study uses Soekanto's role theory which consists of three types, namely: a. Active role; b. Participatory role; c. Passive role. This study uses a qualitative method based on the social constructivism paradigm. In data collection, researchers conducted interviews, observations, and documentation as well as data triangulation regarding the role of the Customary Government in managing mangrove forests in the Women's Forest of Enggros Village. The results of the study show that by using this role theory, it is possible to see the role of Harsori in carrying out its responsibilities in managing customary forests. Then the role of Enggros indigenous women is included in the participatory category, because they provide real contributions to customary forests by consistently maintaining customary forests. However, there are also those who have a passive role in environmental and development problems because they are considered not to provide benefits to them. However, the problem related to undisbursed village funds has become a concern for the community and the local customary council.